"It looks kind of cool when cool people smoke, but…" Norwegian adolescents' decoding of smoking scenes in films. Issue 6 (December 2017) - Sæbø, Gunnar; Scheffels, Janne; Tokle, Rikke
Aims: Exposure to smoking scenes in films is seen as contributing to smoking initiation among young people. This has triggered calls to include depictions of smoking as a criterion in film ratings. All the same time, little is known about how adolescents interpret different smoking scenes. This study analyses how young people decode smoking scenes by contextualising identification with, and evaluation of, various characters who smoke, as well as the significance of film genres. Design: In order to explore how adolescents conceptualize smoking scenes in different film genres, we conducted eight focus-group interviews with adolescents aged 13–17 years ( n = 54), using purposive sampling. The discussions were semi-structured with a standard guide, and we used clips from eight films containing various positive and negative moods and character types as stimuli for the discussions. To analyse interpretations qualitatively, thematic coding was applied. Results: The adolescents acknowledged that smoking is a narrative ingredient designed to illustrate and amplify character traits and situational moods. Characters who smoked were usually interpreted in terms of smoking stereotypes: stress relief, romantic seduction, social interaction between equals, habitual smoking, and as a symbol of "bad guys". The adolescents identified more strongly with elegant, positive, and self-assured smoking characters than with negative, anxious, or ambiguous characters. Conclusions: Adolescents interpret smoking scenes in accordance with encoded meanings: they tend to get the messages inscribed by the filmmakers. As positive and glamorous representations are more likely to stimulate smoking experimentation and initiation among adolescents than negative representations, future research should distinguish more clearly between exposure to positive and to negative representations.